The Influence of Hemoglobin Levels and Nutritional Status of First-Trimester Pregnant Woman with Low Birth Weight - Kolifah; Srirahandayani, Dwi; Prihartanti, Niken Grah; Mudhawaroh (Jurnal Kesehatan Komunitas Indonesia, 2023)
Premature birth is identified as the most significant contributor to infant mortality. The weight of a newborn baby is determined by nutritional status at the time of conception. Pregnant women who are malnourished and experience physical weakness will endanger the mother's life and threaten the safety of the fetuce. LBW can be caused by anemia, inadherence to antenatal care, mothers with chronic diseases and smoking. This study aimed to determine the influence of hemoglobin levels and nutritional status of first-trimester pregnant women with low birth weight events. This type of quantitative research is a retrospective design. The population are mothers who gave birth at the Kabuh Community Health Center, Jombang Regency, in April 2019 obtained a sample of 39 respondents using a purposive sampling, with inclusion criteria birthing mothers have a KIA book. The data were analyzed using logistic regression. The results showed that almost all (79.5%) 31 pregnant women were not anaemic, almost all (84.6%) 33 pregnant women had normal nutritional status and almost all (76.9) babies were born with average weight, namely 30 respondents. There is a relationship between Hemoglobin  levels in pregnant women and the incidence of LBW with a value of p = 0.000. There is a relationship between the nutritional status of pregnant women and the incidence of LBW with a value of p = 0.000. The most dominant factor is Hb levels (p=0.001 exp B:30) Pregnant women are anaemic, one of the factors causing poor nutritional status. Nutritional status lacks calorie energy, inhibiting the fetus's nutritional intake, resulting in premature labour or disruption of fetal growth.